An alternative evaluation method for friction condition in cold forging by ring with boss compression test - Hu, Chengliang; Ou, Hengan; Zhao, Zhen (Elsevier, 2015)
Ring compression test (RCT) is a very popular method used to quantitatively evaluate friction condition sat the tool–workpiece interface by measuring the variations of the inner diameter of the ring in metal forming. There are many possibilities for measuring the inner diameter variations in RCT because of non-uniform deformation of the inner hole during the test. Such non-uniform deformation of the inner hole causes difficulties in precise measurement of the inner diameter and hence the accuracy of the derived friction coefficient. To avoid the disadvantage in dimension measurement of the conventional RCT, an alternative method for evaluating friction conditions in cold forging named ring with boss compression test (RCT-B) is proposed. By the introduction of the RCT-B concept, finite element simulation results under different friction conditions were obtained. Results showed that the shape of the outer boss remains stable during the compression deformation and allows the diameter of the outer boss to be measured more easily and accurately. The calibration curves of the RCT-B concept were constructed by using FE simulation, which cover the range of friction conditions in cold forging process. Finally, the RCT-B method was successfully applied to determine the friction factors of four different lubricating conditions in compression of aluminum rings. Furthermore, the phenomena with different lubricating conditions between the upper and lower die–workpiece interfaces were also studied using both simulation and experimental testing. The results show that it is possible to quantitatively assess the difference of friction conditions at the upper and lower die–workpiece interfaces by simply checking the inclined angle of the outer boss with the RCT-B method.